2023
DOI: 10.1186/s12886-023-02824-5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications after successful primary rhegmatogenous retinal detachment repair

Abstract: Background To evaluate the incidence and risk factors for cystoid macular edema (CME) and epiretinal membrane (ERM) development after surgery for primary rhegmatogenous retinal detachment (RRD). Methods Retrospective observational cohort study involving 62 consecutive patients with primary RRD who underwent RRD repair with either scleral buckling (SB) or pars plana vitrectomy (PPV). SB was used in young phakic patients without posterior vitreous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It is debated whether the ILM should be peeled in RD surgery to avoid the secondary formation of ERM [ 21 ]. The i-OCT guided the surgeon in deciding when to avoid the ILM peeling in cases of significant thinning of the fovea ( Figure 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is debated whether the ILM should be peeled in RD surgery to avoid the secondary formation of ERM [ 21 ]. The i-OCT guided the surgeon in deciding when to avoid the ILM peeling in cases of significant thinning of the fovea ( Figure 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative epiretinal membrane formation, also known as macular pucker, is another reported complication affecting between 1.7% and 33.3% of patients [ 38 , 45 , 54 , 56 , 64 , 67 , 69 ]. In a study that examined the incidence of epiretinal membrane formation after successful primary RRD repair, postoperative epiretinal membranes developed in 15% and 28.5% of patients in the scleral buckling and PPV groups, respectively [ 113 ]. Similarly, a meta-analysis revealed that the incidence of epiretinal membrane formation was 7.1% and 5.2% in patients treated with PPV and scleral buckling alone, respectively [ 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…CME is a primary cause of reduced vision following both cataract and vitreoretinal surgery. 3 , 4 , 10 …”
Section: Discussionmentioning
confidence: 99%